Electrically Tuned Microwave Devices Using Liquid Crystal Technology - Pouria Yaghmaee; Onur Hamza Karabey; Bevan Bates; Christophe Fumeaux; Rolf Jakoby (International Journal of Antennas and Propagation)
An overview of liquid crystal technology for microwave and millimeter-wave frequencies is presented. The potential of liquid crystals as reconfigurable materials arises from their ability for continuous tuning with low power consumption, transparency, and possible integration with printed and flexible circuit technologies. This paper describes physical theory and fundamental electrical properties arising from the anisotropy of liquid crystals and overviews selected realized liquid crystal devices, throughout four main categories: resonators and filters, phase shifters and delay lines, antennas, and, finally, frequency-selective surfaces and metamaterials.